Adaptability of grain sorghum cultivars for saline soils of Rio Grande do Norte state, Brazil - Fernandes, Mário Bezerra; Castro, Jadilson Rubens de; Aquino, Boanerges Freire de; Fernandes, Vera Lúcia Baima; Alves, José Solon; Góis, Francisco César de (Pesquisa Agropecuaria Brasileira, 1992)
Five grain sorghum cultivars (Sorghum bicolor (L.) Moench) previously selected on a selection trial, were grown in saline soils in order to test their ability to produce in salt concentrated environments. The experiment was conducted for three years in a completely randomized block design with five treatments and three replications; the treatments represented the following cultivars: IPA 0007, IPA 0073, IPA 1011, IPA 1131 and EA 116. The stability and adaptability analysis, which included weights of both on thousand seeds and total seeds, revealed that some cultivars are salt tolerant and others are not. The salt tolerant cultivars were the EA 116 and IPA 1011 with high performance in grain yield; the other ones, in the face of the low performance in grain yield, could by considered as not appropriated to be grown in saline environments.
Keywords: Sorghum bicolor; salt; agro-economical viability